Collaboration Governance On Ecotourism Belitung Unesco Global Geopark - Wahyudi Utomo; Effy Rusfian; Martani Huseini (Journal Of Social Science (JoSS), 2024)
This study aims to analyze the governance of collaboration of the Belitung Ecotourism UNESCO Global Geopark. Attention is given to the study of collaboration governance considered one of the key issues of success in the context of Belitung tourism development as part of the UNESCO Global Geopark network. The contribution and role of each actor whether from the government, private sector, community, or community has made a positive contribution to building sustainable and environmentally sound tourism quality. This research uses a sequential mixed methods research exploratory approach, in this research data is obtained through in-depth interviews, document reviews, and surveys so that the triangulation process can be carried out more completely. Research informants consisted of elements of government, the private sector, associations, society, and communities. A total of 13 informants were interviewed and 31 people responded to the survey. The results show that trust, values, and social networks have become the glue and bind each actor so that they function as a basic element to form a good collaboration.